Media Pamflet dan Alat Peraga Phantom dalam Rangka Meningkatkan Pengetahuan Karies Gigi pada Anak - Mariana Koch, Novarita; Raule, Jean Henry; Bugis, Sartika (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Knowledge is acquired in education from an early age including elementary school. Elementary school children are the main target for improving dental health. This improvement requires appropriate promotional media to support dental health promotion so that a theoretical understanding of the related material can be achieved. This research aims to evaluate the effectiveness of pamphlet media and demonstration of dental phantom props on children's knowledge level of dental caries. The study was conducted with a Quasi-Experimental research type with a